Peran Literasi Keuangan dan E-commerce dalam Membentuk Perilaku Konsumtif - Irawati (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the influence of financial literacy and e-commerce on the consumer behavior of students of the Faculty of Economics and Business, Class of 2022, Universitas Teknologi Sumbawa. With increasing access to e-commerce platforms and growing financial literacy, it is important to understand the factors that influence students' consumer behavior. This study uses a quantitative approach with a multiple linear regression method, involving 100 respondents who are students of the Faculty of Economics and Business. The results of the study show that financial literacy has a negative and significant effect on students' consumer behavior, which means that the higher the level of financial literacy of students, the lower their tendency to engage in consumer behavior. Conversely, e-commerce has a significant positive effect on consumer behavior, which indicates that the more often students engage in e-commerce transactions, the higher their consumer behavior. With an R-square value of 0.876, this study shows that financial literacy and e-commerce can explain 87.6% of the variability in students' consumer behavior. This study provides important implications for improving financial literacy among students and managing wiser consumer behavior through more responsible use of e-commerce.